Conformity of English Textbooks for Seventh Grade with Curriculum 2013 - Athia Fidian; Nanik Supriani (Journal of English Language and Pedagogy, 2018)
This research is aimed to find out the conformity between the materials in the English textbooks for the seventh grade Junior High School with the basic competences in the syllabus of English Curriculum. This research belongs to an evaluation research. In this study, four kinds of English textbook for the seventh grade of junior high school; ‘When English Rings The Bells’, ‘Let’s Speak English’, ‘Bright’, and ‘Headline English’, were  analyzed  based on 2013 English curriculum. The instruments used in this research was a checklist on teachers’ interview and also students’ interview. The data in this research were analyzed by using 14 criteria according to Tomlinson (2008) to evaluate the course book. Findings show that the materials in the textbooks do not conform to the basic competences in the syllabus. This study shows that not all the content of the textbooks conform to the basic competences in the syllabus of English Curriculum 2013. Beside that some of books also don’t meet the learners want and need. Another finding is that those books had its strengths and weaknesses. Those books provide varied activities and texts and develop character buildings. Besides, they are visually attractive. On the other hand, they did not include material for pronunciation.